The localities as institutions of Democratic government: Theory and praxis (2013)
In this article we will treat the problem of civic participation with the objective of responding to the problematic of whether the localities (localidades), as political and administrative divisions of Bogota, constitute, in and of themselves, institutions of democratic government; that is, whether they are an appropriate and efficient government authority to consolidate civic participation processes, holding shared power over decisions and shared responsibility over the city's political processes.